Digital Health COVID-19 Impact Assessment: Lessons Learned and Compelling Needs - Lee, Peter; Abernethy, Amy; Shaywitz, David; Gundlapalli, Adi V.; Weinstein, James; Doraiswamy, P. Murali; MD, Kevin Schulman; Madhavan, Subha (NAM Perspect, 2022)
This discussion paper is part of the National Academy of Medicine’s Emerging Stronger After COVID-19: Priorities for Health System Transformation initiative, which commissioned papers from experts on how 9 key sectors of the health, health care, and biomedical science fields responded to and can be transformed in the wake of the COVID-19 pandemic.